(3JaSjQ GdbQBf GdYXjes - (3Ydj Hf eMeO MHjH, CHh GdMSf GdeGhQOj,J (B450 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI Wg Hbhdg (B: (3Wg GSe ef CSeGA QShd Gddg Udi Gddg Ydjg hSde , hai GdMOjK (B: (3di YfO QHi YTQI CSeGA s
(3BNQgG (B:s
(3ChGNQ GdBi Ydi fXe hGMO , hddg CYde , hgPG BNQ eG GfJgi EdjfG ef JaSjQ GdbQBf GdYXje s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HChdgG Jedc SfI (B1125(3g`s
(3cJHJ CSeGA GdShQ HGdMeQIs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B189s
Keywords: (3GdJaSjQ hYdhe GdbQBfs